DIGITAL HUMAS PEMERINTAH DALAM MENYAMPAIKAN INFORMASI EDUKASI PENCEGAHAN COVID-19 DI INDONESIA - Novita Damayanti; Cakra Ningsih (Universitas Prof. Dr. Moestopo (Beragama), 2020)
This research aims to find out the government's digital public relations in conveying information on Covid-19 prevention education in Indonesia. The concept used is 7-Cs public relations communication, consisting of: credibilty, contex, content, clarity, continuity, and consistency, channels, capability of the audinence. Government public relations, digital public relations, roles and PR models. The paradigm in this study is Constructivist. This type of research is qualitatively descriptive. The method used is a case study. Research findings show the Ministry of Communication and Information, as well as the ministry of SOEs carry out the functions and roles of government public relations by providing messages or information to the Indonesian people related to Covid-19. The role of communicator facilitator runs in the case of Covid-19 where actively and synergistally between institutions convey information to the public, the message is not only conveyed but also adapted to the conditions of the community that will receive the message.